Aksiologi Ilmu Dalam Perspektif Barat Dan Islam - Adi Sulistyo Wibowo; Aidatun Nisrina Nurul Firdaus; Ahmad Fathir Qodri; M. Effendi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Axiology breaks down social values, symbolic and physical-material aspects into things that must be fulfilled in the application of scientific disciplines. Axiology is a parameter of truth, morals and ethics that functions as the normative basis of science. The aim of this research that the author wants to achieve in writing this paper is: To find out the axiology of science. To know the axiology of science from a Western perspective, To find out the axiology of science from an Islamic perspective. The conclusion of axiological research is a study of scientific values ​​or the usefulness of science from both western and Islamic perspectives viewed from a philosophical perspective. Axiology, which is essentially the study of values, has given rise to a branch of discussion that focuses on good and bad values, namely Ethics. Ethics is a theory about human behavior that is viewed from a good and bad angle using the standard of human reason.